The effects of Baduanjin exercise on physical fitness and mental health of female college students - Xinmin Zhao; Kai Nan; Tongtong Xing (Physical Education of Students, 2024)
Background and Study Aim. In the context of increasing stress and declining health among female college students, there is an urgent need for effective methods to enhance their physical and mental well-being. The aim of this study is to analyze the impact of Baduanjin exercise on the physical fitness and mental health of female college students.